2023
DOI: 10.1101/2023.03.15.532673
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The bromodomain inhibitor JQ1 is a molecular glue targeting centromeres

Abstract: Centromeres are essential for cell proliferation and a promising target for anti-cancer therapies, yet no drugs have been identified that specifically target centromeric chromatin. To identify candidates, we analysed chromatin proteins at repetitive loci using a novel big-data approach and discovered the bromodomain protein BRD4 localises to centromeres, a localisation enhanced by the bromodomain inhibitor JQ1. While bromodomain inhibitors typically prevent BRD4 from binding chromatin, we found that JQ1 stabil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 62 publications
1
0
0
Order By: Relevance
“…We found that K36me3 partitions between eu- and heterochromatin. The presence of K36me3, a mark globally associated with active chromatin, at H3K9-methylated heterochromatin has also been observed in other studies ( 3 , 84 ) and been described in human datasets ( 93 , 94 ). Such overlap of active with more repressive chromatin features may not simply be due to population heterogeneity since engineered dual readers validated the existence of such dual domains ( 84 , 95 ) and have been proposed to bookmark poised enhancers genome-wide in mouse ( 84 ).…”
Section: Discussionsupporting
confidence: 75%
“…We found that K36me3 partitions between eu- and heterochromatin. The presence of K36me3, a mark globally associated with active chromatin, at H3K9-methylated heterochromatin has also been observed in other studies ( 3 , 84 ) and been described in human datasets ( 93 , 94 ). Such overlap of active with more repressive chromatin features may not simply be due to population heterogeneity since engineered dual readers validated the existence of such dual domains ( 84 , 95 ) and have been proposed to bookmark poised enhancers genome-wide in mouse ( 84 ).…”
Section: Discussionsupporting
confidence: 75%